PENGARUH CAPITAL INTENSITY, STRATEGI BISNIS DAN UMUR PERUSAHAAN TERHADAP TAX AVOIDANCE - Yohana Febrianti Efendi Putri; Irwan Setiawan (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of Capital Intensity, Strategy Business and Company Age on Tax Avoidance in property and real estate companies listed on the Indonesia Stock Exchange in 2016-2020. The population of this research is property and real estate companies listed on the Stock Exchange in 2016-2020 as many with a sample selection technique using purposive sampling and obtained 24 samples of companies with a 5 year research period. So the data analyzed amounted to 120 sample data of property and real estate companies listed on the IDX for the period 2016-2020. The data analysis technique used was Linear Regression Analysis with Panel Data with the help of the Eviews 12 program. The results showed that the Capital Intensity variable has no effect on Tax Avoidance with probability value of 0.7296 , the Strategy Business variable had a significant negative effect on Tax Avoiance with probability value of 0.0047 and the Company Age variable had a significant negative effect on Tax Avoidance with probability value of 0.0021, as well as the Capital Intensity, Strategy Business and Company Age variables simultaneously have a significant effect on Tax Avoidance